Penggunaan Digital Marketing dalam Menjalankan Usaha Laundry Agios Living oleh Pengurus Santri dan Santriwati di Pondok - Mukti, Anggoro; Raharjo, Raden Johnny Hadi (Universitas Pahlawan Tuanku Tambusai, 2025)
In the context of rapid digitalization, the utilization of information technology has become essential for business operators, including among students in pesantren (Islamic boarding schools). This community service activity aims to enhance understanding and skills in using digital marketing for laundry businesses at Pondok Agios Living. The methods employed include three phases: socialization, mentoring and training, and simulation and trial. The results indicate that digital marketing training provides new insights for the managers in managing their businesses. Additionally, transaction simulations offer concrete experiences that boost the confidence and capabilities of the managers in customer service. By leveraging digital marketing, it is expected that the laundry business can increase visibility, expand market reach, and enhance customer satisfaction.